Improvement of antifouling resistance of polymer membranes using CuO nanoparticle incorporation-long-term performance evaluation - Szwast, Maciej; Polak, Daniel; Krasiński, Andrzej (Chemical and Process Engineering: New Frontiers, 2026)
Long-term biofouling significantly limits continuous membrane filtration operated under constant transmembrane pressure, causing progressive hydraulic resistance and permeate flux instability. This study examined the long-term performance of polypropylene capillary membranes modified with a thin polysulfone layer containing CuO nanoparticles under cross-flow microfiltration with Escherichia coli. The focus was on operational stability during extended filtration rather than short-term material properties. Scanning electron microscopy, X-ray fluorescence, and capillary porosimetry confirmed that the modification was confined to the near-surface region without altering intrinsic pore structure or initial hydraulic permeability. Ninety-sixhour continuous filtration tests showed similar initial fluxes for both membranes. However, CuO-modified membranes exhibited a markedly slower flux decline. Consequently, cumulative permeate production was approximately 43% higher compared to unmodified membranes. Hermia model analysis indicated that fouling followed the intermediate pore-blocking mechanism in all cases. To account for time-dependent biofouling dynamics, the model was extended using a Weibull formulation, allowing separation of fouling time scale from intensity. The generalized model revealed a lower initial fouling rate and significantly longer characteristic fouling time for CuO-modified membranes, indicating delayed transition to high-resistance conditions. From a process-engineering standpoint, bacteriostatic surface modification effectively enhances long-term operational stability.